Cuidados de enfermería en el consumo de sustancias psicotrópicas en embarazo de adolescentes en el “Centro de Salud Febres Cordero” Guasmo Sur Guayaquil durante el periodo mayo a septiembre 2019. - Damiani León, Jean Carlos (2019)
The problem of the study is related to the consumption of drugs by teenage pregnant women, in this way, the objective of determining nursing care in the consumption of psychotropic substances in teenage pregnancy was raised, in the “Febres Health Center Lamb” Guasmo Sur Guayaquil, during the period May to September 2019. The descriptive, quantitative methodology was applied, using the survey of pregnant minors, whose results showed that 76% are 16 to 19 years old, 52% have instruction primary school, they have been using marijuana and heroin for one to three years, observing limitations in the delivery of informational material (45%), counseling and emotional support with 60%, in addition to poor integration between family members and pregnant teenagers who consume drugs (51 %). In conclusion, defects were found in the execution of the educational and nursing care role, which generated dissatisfaction in 49% of pregnant adolescents addicted for non-compliance with nursing care in reference, recommending a specialized training plan for nursing professionals, in caring for patients in a state of gravity who use drugs.